Potential Contributions of Clinical and Community Testing in Identifying Persons with Undiagnosed HIV Infection in the United States. (3rd September 2020) - Kahn, James G.; Bendavid, Eran; Dietz, Patricia M.; Hutchinson, Angela; Horvath, Hacsi; McCabe, Devon; Wolitski, Richard J.
Background: An estimated 166, 155 individuals in the United States have undiagnosed HIV infection. We modeled the numbers of HIV-infected individuals who could be diagnosed in clinical and community settings by broadly implementing HIV screening guidelines. Setting: United States. Methods: We modeled testing for general population (once lifetime) and high-risk populations (annual): men who have sex with men, people who inject drugs, and high-risk heterosexuals. We used published data on HIV infections, HIV testing, engagement in clinical care, and risk status disclosure. Results: In clinical settings, about 76 million never-tested low-risk and 2.6 million high-risk individuals would be tested, yielding 36, 000 and 55, 000 HIV diagnoses, respectively. In community settings, 30 million low-risk and 4.4 million high-risk individuals would be tested, yielding 75, 000 HIV diagnoses. Conclusion: HIV testing in clinical and community settings diagnoses similar numbers of individuals. Lifetime and risk-based testing are both needed to substantially reduce undiagnosed HIV.